Effect of progesterone supplementation on post-coital unilaterally ovariectomized superovulated mice in relation to implantation and pregnancy - Bhattarai, Tirtha; Datta, Soumita; Chaudhuri, Prasenjit; Bhattacharya, Koushik; Sengupta, Pallav (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Unilateral ovariectomy (ULO) and its consequences with endocrine replacement in pregnant mice are important to examine both follicular dynamics as well as the outcome of implantation and pregnancy. In mice, ovariectomy on fourth day morning (D4), before pre-implantation estrogen secretion induces delayed implantation and embryonic diapauses, i.e. a state of suspended animation of embryos. The present study has been undertaken to evaluate the effect of progesterone supplementation on rate of implantation in unilaterally ovariectomized superovulated mice. Our study reveals that progesterone (P4) may help to protect the loss of embryo before and after the implantation if ULO is done during pre-implantation period (D4). The present study also shows if ovary is present in one side of the animal, it secretes estrogen (E2) in circulation which acts systematically on the uterus rather than locally. The findings of the present study show that progesterone may help to avoid the loss of embryo before and after the implantation, if ULO is done during pre-implantation period (D4) and the serum estrogen (E2) acts systematically on the uterus. Thus, it can be concluded that implantation in the uterine horn where ovary is not there.